Odpowiedź :
G
[tex]g) \: (3 \sqrt{50} + 2 \sqrt{68} - \sqrt{32} ) \div \sqrt{2 } = \\ \\ \frac{3 \sqrt{50} + 2 \sqrt{68} - \sqrt{32} }{ \sqrt{2} } = \\ \\ \frac{15 \sqrt{2} + 4 \sqrt{17} - 4 \sqrt{2} }{ \sqrt{2} } = \\ \\ \frac{11 \sqrt{2} + 4 \sqrt{17} }{ \sqrt{2} } \times \frac{ \sqrt{2} }{ \sqrt{2} } = \\ \\ \frac{(11 \sqrt{2} + 4 \sqrt{17} ) \times \sqrt{2} }{ \sqrt{2} \times \sqrt{2} } = \\ \\ \frac{22 + 4 \sqrt{34} }{2} = \\ \\ \frac{2(11 + 2 \sqrt{34}) }{2} = 11 + 2 \sqrt{34} [/tex]
H
[tex]h) \: 4 \sqrt[3]{54} + \sqrt[3]{16} - \sqrt[3]{128} = \\ 12 \sqrt[3]{2} + 2 \sqrt[3]{2} - {2}^{2} \sqrt[3]{2} = \\ 12 \sqrt[3]{2} + 2 \sqrt[3]{2} - 4 \sqrt[3]{2} = 10 \sqrt[3]{2} [/tex]
__
[tex] {3}^{2} \times \frac{1}{243} \times ( {81})^{2} \times {3}^{ - 3} = \\ \\ {3}^{2} \times \frac{1}{ {3}^{5} } \times {3}^{8} \times {3}^{ - 3} = \\ \\ \frac{1}{ {3}^{3} } \times {3}^{8} \times {3}^{ - 3} = \\ {3}^{5} \times {3}^{ - 3} = {3}^{2} [/tex]